CIREBON PALACES IN THE DIGITAL ERA - Ina Helena Agustina; Astri Mutia Ekasari; Irland Fardani; Hilwati Hindersah (Lembaga Penelitian Universitas Pasundan, 2019)
Keraton is a result of the creation from the past. In order to compete in the digital era, Keraton has to make an advancement which is inline to the development of the digital era. The aim of this paper is to describe the existentialism concept of Keraton Kasepuhan, Keraton Kanoman, and Keraton Kacirebonan, which are located in the city of Cirebon, in the digital era. The method used in this research is the qualitative-descriptive approach of the phenomena which appear in the field. The results are then matched with the theory to form the conclusion of the existentialism concept of the Keraton in this digital era. The obtained concept can be utilized as an example for other Keraton in Indonesia to retain their existence especially for the generation of millennials.